Analysis of the Relationship Between Hospital Ownership and Google Maps Star Ratings: A Case Study of Regional General Hospitals (RSUD), Private Hospitals, and Muhammadiyah Hospitals (RSM) in East Java - Absor, Sholihul; Rochmah, Thinni Nurul; Musa Ghufron; Rezy Ramawan Melbiarta (Universitas Muhammadiyah Surabaya, 2025)
The Muhammadiyah Hospital network (RSM) is a religious non-profit oriented facilities in Indonesia which emphasizing ethical or faith-based considerations, in approach to providing services. RSM faces the challenge of excelling compared to its competitors, including Regional General Hospitals (RSUD) and other private competitor hospitals. This study aims to examine the relationship between hospital ownership status and Google star ratings among hospitals in East Java. A cross-sectional study was conducted involving 31 RSM, 19 RSUD, and 20 private competitor hospitals, which were compared in their respective cities. Kruskal-Wallis test was performed to compare the Google rating between each ownership, and simple logistic regression was performed to examine the association between hospital ownership and Google star rating. Of 31 regions, private hospitals (both competitor and RSM) had the highest rating in 22 regions when compared in their respective region. Private competitor hospital had the highest median (4.2 (3.9-4.7)), followed by RSM (4.1 (3.1-4.7)) and RSUD (4.0 (2.8-4.8)). Generally, a significant difference was found between RSUD and private competitor hospital (p<0.05), while between RSM and private competitor or RSUD were not significant. Logistic regression showed a significant association between hospital ownership and Google rating, with being a private competitor being likely to have a higher rating compared to RSUD (OR (95% CI): 8.10 (1.46-45.06)). In conclusion, our findings suggest hospital ownership had significant association with Google ratings, specifically between private competitor and public hospitals. While RSM didn’t have any significant association although they tend to have higher ratings to RSUD.